Prognostic factors for mortality in pediatric acute poststreptococcal glomerulonephritis - Syamsul Nur; Husein Albar; Dasril Daud (Indonesian Pediatric Society, 2016)
Background Acute post-streptococcal glomerulonephritis (APSGN) is one of the most common causes of glomerular disease in developing countries, including Indonesia. It can lead to end stage renal failure and higher mortality rates. To decrease morbidity and mortality, it is important to understand the prognostic factors affecting the disease.Objective To identify prognostic factors affecting outcomes in pediatric APSGN patients.Methods Study data were collected from medical records of patients with APSGN hospitalized in Wahidin Sudirohusodo Hospital, Makassar in 2009-2013. Possible prognotic factors analyzed were gender, age, nutritional status, level of consciousness, as well as proteinuria, hemoglobin, serum albumin, urea, and creatinine levels.Results Of 86 subjects, 82 (95.3%) survived and 4 (4.7%) died. Fifty-three (61.6%) patients were male and 33 (38.4%) were female. Subjects’ ages ranged from 3.42 to 14.67 years, with a mean age of 9.36 years. Multivariate analysis revealed serum creatinine level >1.5 mg/dL to be an independent prognostic factor for mortality in children with APSGN (AOR 15.43; 95%CI 1.31 to 181.7; P=0.03).Conclusion High serum creatinine level is an independent prognostic factor for poor outcomes in children with APSGN. [Paediatr Indones. 2016;56:166-70.].